Mannan Oligosaccharide Enhanced the Growth Rate, Digestive Enzyme Activity, Carcass Composition, and Blood Chemistry of Thinlip Grey Mullet (Liza ramada) - Fawzy I. Magouz; Mohamed I. Bassuini; Malik M. Khalafalla; Ramy Abbas; Hani Sewilam; Salama Mostafa Aboelenin; Mohamed Mohamed Soliman; Asem A. Amer; Ali A. Soliman; Hien Van Doan; Mahmoud A. O. Dawood (Animals, 2021)
Mannan oligosaccharide (MOS) is prebiotic with high functionality in aquaculture. The current study investigated the potential roles of MOS on the growth performance, digestive enzyme activity, carcass composition, and blood chemistry of Thinlip grey mullet (Liza ramada). Four tested diets with 34.49% crude protein and 6.29% of total lipids were prepared and fortified with 0, 0.5, 1, and 2% MOS. Fish of initial weight = 5.14 ± 0.11 g/fish were distributed in 12 hapas (0.5 × 0.5 × 1 m) at 15 fish per hapa (triplicates) and fed the test diets to the satiation level two times a day (08:00 and 15:00) for eight weeks. At the end of the trial, all fish were weighed individually for growth performance calculation. Blood was collected to check blood chemistry traits, and intestines were dissected for digestive enzyme analysis. Fish treated with MOS had marked enhancement in the final body weight, feed conversion ratio, protein gain, and protein retention regardless of inclusion dose (p < 0.05). The weight gain, specific growth rate, and protein efficiency ratio were meaningfully enhanced by including MOS at 0.5 and 1%, followed by fish fed with 2% MOS, while the lowest values were in the control group (p < 0.05). Insignificant influences of MOS were seen on the chemical composition of carcass components (moisture, crude protein, total lipids, and ash) (p > 0.05). Fish treated with MOS at 0.5 and 1% had marked enhancement in the amylase, lipase, and protease activities regardless of inclusion dose (p < 0.05). The blood total protein and albumin levels were meaningfully enhanced by including MOS at 0.5 and 1%, followed by fish fed with 2% MOS, while the lowest values were in the control group (p < 0.05). The blood globulin was significantly enhanced in fish fed 1% MOS than fish treated with 0, 0.5, and 2% of MOS (p < 0.05). The blood lysozyme activity was meaningfully enhanced by including MOS at 1%, followed by fish treated with 0.5 and 2%, while the lowest values were in the control group (p < 0.05). Phagocytic activity and phagocytic index were markedly improved in fish treated with 1 and 2% MOS, followed by those fed 0.5% compared with fish fed MOS-free diet (p < 0.05). Superoxide dismutase and glutathione peroxidase were markedly improved in fish treated with 1, and 2% MOS, followed by those fed 0.5% compared with fish fed MOS-free diet (p < 0.05). Dietary MOS (0.5, 1, and 2%) meaningfully enhanced catalase activity while decreased the malondialdehyde concentration (p < 0.05). In summary, dietary MOS is required at 0.5–1% for enhancing the growth rate, feed efficiency, digestive enzyme activity, blood chemistry, and antioxidative capacity of grey mullet.